Daily mobility, activity and environmental determinants of stress in ecological momentary assessment (EMA) and GPS studies: a scoping review protocol - Guy Fagherazzi; Camille Perchoux; Noemie Topalian (BMJ Open, 2025)
Introduction Stress is omnipresent in our everyday lives and a key risk factor for our physical and mental health. Yet little is known about the impact of geographic life environments, linked to our daily activities and mobility patterns, on our momentary and daily stress levels.We propose this review to gather evidence on the spatio-temporal determinants of momentary or daily stress in studies using ecological momentary assessment (EMA) or experience sampling methods (ESM) in addition to global positioning systems (GPS) tracking. We will focus on the spatio-temporal definition and modelling of environmental exposures accounting for participant daily activities and mobility patterns and their association with stress.Methods and analysis This scoping review will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses framework for scoping reviews (2018). We will search the PubMed/Medline, Web of Science, PsycInfo and Scopus databases. We will include papers using EMA or ESM and GPS measuring chronic, daily or momentary stress as an outcome; these methods are also referred to as geographically-explicit ecological momentary assessment.Articles published from January 2000–June 2025 will be screened. Two independent reviewers will screen titles and abstracts to agree on the inclusion of articles. No geographical or population limitation will be imposed.Ethics and dissemination This study is a scoping review based on previously published and publicly available literature. It does not involve the collection of primary data, human participants, or the processing of personal or sensitive information. Therefore, ethical approval is not required in accordance with institutional and international research ethics guidelines. The results will be submitted in peer-reviewed journals and presented at international conferences.